2014
DOI: 10.1007/s00261-014-0278-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole-organ and segmental stiffness measured with liver magnetic resonance elastography in healthy adults: significance of the region of interest

Abstract: PurposeMR elastography (MRE) is a recent non-invasive technique that provides in vivo data on the viscoelasticity of the liver. Since the method is not well established, several different protocols were proposed that differ in results. The aim of the study was to analyze the variability of stiffness measurements in different regions of the liver.MethodsTwenty healthy adults aged 24–45 years were recruited. The examination was performed using a mechanical excitation of 64 Hz. MRE images were fused with axial T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…Finally, 31 studies fulfilled the eligibility criteria for our analysis, including eight studies using both GRE and SE‐EPI sequences, 22 studies using only a GRE sequence, , , , , , , , and one study using only an SE‐EPI sequence . As one study using both GRE and SE‐EPI sequences potentially overlapped with a population in another GRE sequence outcome study, we did not include the outcomes of this study in the evaluation of the pooled proportion of technical failure of GRE sequences, but used it only for the head‐to‐head comparison between GRE and SE‐EPI sequences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 31 studies fulfilled the eligibility criteria for our analysis, including eight studies using both GRE and SE‐EPI sequences, 22 studies using only a GRE sequence, , , , , , , , and one study using only an SE‐EPI sequence . As one study using both GRE and SE‐EPI sequences potentially overlapped with a population in another GRE sequence outcome study, we did not include the outcomes of this study in the evaluation of the pooled proportion of technical failure of GRE sequences, but used it only for the head‐to‐head comparison between GRE and SE‐EPI sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The demographic characteristics of the included studies are shown in Table . In brief, subjects were enrolled prospectively in 16 studies and retrospectively in 15 studies , , , , , , , . The mean patient ages in 14 studies , , , , , , , , ranged from 25 to 60.5 years, but we could not analyze patient age in the other studies, because they did not report demographic information on all subjects, but reported only those with successful examinations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All liver stiffness measurements were made while remaining blinded to measurement values obtained with other sequences in the same patient. Liver stiffness values for each MR elastography examination were expressed as a mean of mean stiffness measurements (in kilopascals) from each of four axial sections through the mid liver, as this has previously been defined as a reproducible method of measuring liver stiffness (18).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the standard anatomic evaluation of liver morphology, MRE performs significantly better for both significant fibrosis (0.989 in MRE vs 0.71 to 0.82 in MRI) and cirrhosis (0.935 in MRE vs 0.61 to 0.80 in MRI) 16. Using a 3.7-kPa cutoff value, the study by Venkatesh et al 6. found that MRE yielded a sensitivity of 91% and specificity of 80% for differentiating F0–F2 from F3–F4 grades of fibrosis.…”
Section: Introductionmentioning
confidence: 99%